Production of Transglycosylated Rutin Using Novel Cyclodextrin Glucanotransferase - Sun, T.; Jiang, B.; Pan, B.L. (Asian Journal of Chemistry, 2013)
Besides physical and chemical methods, the enzymatic method could be applied on the modification of rutin molecule. In this study, the transglycosylation of rutin using novel cyclodextrin glucanotransferase (CGTase) produced by Bacillus sp. SK13.002 has been investigated. The optimization of enzymatic reaction conditions using orthogonal experimental design has also been carried out based on temperature, pH, the amount of enzyme cyclodextrin glucanotransferase and the reaction time. The results indicated that among these enzymatic reaction conditions reaction time is the most important variable. Under the optimized enzymatic reaction conditions of pH 5.5, temperature 35 ºC, 20 U cyclodextrin glucanotransferase per mL reaction system and 24 h of reaction time, the transglycosylation conversation rate of rutin could reach as high as 65.7 %. Furthermore the change of the components of transglycosylated rutins during the rutin transglycosylation has also been investigated.